2023
DOI: 10.2196/45677
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Social Isolation Trajectories and Incident Cardiovascular Disease Among Middle-Aged and Older Adults in China: National Cohort Study

Abstract: Background Although the association between social isolation and the risk of subsequent cardiovascular disease (CVD) is well documented, most studies have only assessed social isolation at a single time point, and few studies have considered the association using repeatedly measured social isolation. Objective This study aimed to examine the association between social isolation trajectories and incident CVD in a large cohort of middle-aged and older adu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In fact, evidence about the association between social participation or social isolation [defined as a state of complete or near-complete lack of contact between an individual and society ( 26 )] and cardiovascular disease is controversial. In a large cohort of 8,422 middle-aged and older subjects, Guo et al demonstrated that subjects with fluctuating social isolation and consistently high social isolation showed significantly higher risk of incident cardiovascular disease when compared to those with consistently low social isolation ( 17 ). Conversely, in a previous study consisted of 33,538 middle-aged Japanese, Oshio et al reported that social participation had no impact in preventing the onset of heart disease ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, evidence about the association between social participation or social isolation [defined as a state of complete or near-complete lack of contact between an individual and society ( 26 )] and cardiovascular disease is controversial. In a large cohort of 8,422 middle-aged and older subjects, Guo et al demonstrated that subjects with fluctuating social isolation and consistently high social isolation showed significantly higher risk of incident cardiovascular disease when compared to those with consistently low social isolation ( 17 ). Conversely, in a previous study consisted of 33,538 middle-aged Japanese, Oshio et al reported that social participation had no impact in preventing the onset of heart disease ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, among older people who never participate in social activity at baseline, it is largely unknown whether increased participation in social activity in later life is associated with reduced risk of health outcomes. Second, previous results regarding the effect of social participation on heart diseases were inconsistent, some of which indicated protective effect ( 17 ), while others indicated neutral effect ( 18–20 ) in middle aged and older population or general population. Still, for older people, the impact of increased participation in social activity on the new onset of heart diseases remains to be investigated.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, Guo et al have shown that the fluctuating and consistently high social isolation is associated with high risks of developing CVD. However, they only evaluated the association between changes of social isolation and onset of CVD but overlooked the mortality [12]. To our knowledge, how changes in social isolation and loneliness affect the risks of incident CVD and mortality remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness is a self-perceived or subjective feeling of being disconnected from social relationships [17] while social isolation is an objective condition, measured by the number of relationships, participation in social activities, and frequency of social engagements [16,18]. Biopsychosocial modeling has identified loneliness and social isolation, as well as depression, anxiety, and education [19][20][21] , as factors impacting a range of chronic diseases, such as hypertension [16], cardiovascular diseases [18,22], digestive disease [23], and diabetes [18].…”
Section: Introductionmentioning
confidence: 99%